Antioxidants in the Management of Sickle Cell Anaemia: An Area to Be Exploited for the Wellbeing of the Patients - Obeagu, Emmanuel Ifeanyi; Bunu, Umi Omar; Obeagu, Getrude Uzoma; Habimana, Jean Bosco (International Research in Medical and Health Sciences, 2023)
Sickle cell disease (SCD), also known as sickle cell anemia, is an often serious autosomal recessive disorder that occurs when both parents pass the defective gene to their children. When oxygen pressure is low, the biconcave disc shape of red blood cells turns sickle due to the polymerization of defective hemoglobin called HbS, caused by point mutations in the beta-globin gene. In patients with sickle cell disease, red blood cells only last for 10 to 20 days, and the bone marrow cannot replenish them quickly enough. Red blood cells change shape in SCD and become hard, sticky, or sickle-shaped which tends to impede blood flow in the small capillaries. A single nucleotide change (GTG for GAG) in codon six of the globin gene, located on the short arm of chromosome 11, causes sickle cell disease (SCD). As a result, valine displaces glutamic acid at the sixth amino acid position in the globin chain, leading to abnormal production of HbS (sickle hemoglobin), which tends to polymerize under conditions of low oxygen saturation, such as cases occur in the microcirculation. These variables affect the degree of deoxygenation of hemoglobin, pH, intracellular HbF concentration, erythrocyte HbS concentration, and polymerization. Repeated polymerization cycles cause irreversible damage to erythrocyte deformability (RBC), whereas a single polymerization causes a reversible reduction and increased susceptibility to mechanical breakage. The polymerization of HbS is the main factor causing SCD. These variables have an impact on pH, intracellular HbF concentration, erythrocyte HbS concentration, polymerization, and degree of hemoglobin deoxidation. Repeated polymerization cycles cause irreversible damage to red blood cell (RBC) deformity, whereas a single polymerization causes reversible reduction and increased mechanical fragility. As oxygen pressure increases, red blood cells can switch back to this state. The result is followed by a “sickle cell crisis,” a vicious cycle that exacerbates hypoxia and leads to more sickle cell disease. Microvascular circulation can be impeded by these deformed sickle cells, leading to vascular damage, organ infarction, pain, and other symptoms of SCD.
Keywords: Antioxidants; Haemoglobin; Management; Red Blood Cells; Sickle Cell Anaemia